Valores energéticos de alimentos determinados com aves em diferentes idades - Schneiders, José Luiz (2012)
Aimed to determine the energy values and the coefficients of different foods with broilers at different ages, two experiments were conducted: A digestibility and a performance trial. In the digestibility experiment the foods used were corn, soybean meal, soybean processed by steam heated, meat and bone meal, poultry by-produtct, fish meal, wheat bran, crude soybean oil and poultry fat. It was using the method of total excreta collection, with five trials, divided into five age groups (1-8, 11-18, 21-28, 31-38 and 41-48 days old). Were used 675, 450, 225, 180 and 180 broilers, respectively, in a completely randomized design with nine treatments and four replicates, totaling 36 experimental units. The second experiment evaluated the performance of broilers and the carcass yield using diets with the metabolizable energy values of corn, soybean meal and soybean oil obtained on the digestibility experiment at different ages. The animals were divided into stages 1-7, 8-21, 22-42 and 43-49 days of age. Four experiments were conducted, divided in phases according to ages: pre-starter, starter, grower and finish, were used, respectively 924, 924, 840 and 672 birds randomly distributed in 42 experimental units in a completely randomized design with seven treatments and six repetitions. At 42 and 49 days old two birds per pen were slaughtered to determine carcass yield, cuts and abdominal fat. Among the plant foods studied, the lower coefficients of apparent digestibility were obtained with wheat bran. Among the animal foods, the meat and bone meal had lower CMA and CMAn. Were adjusted to the LRP model the equations to the CMA of corn, soybean meal and soybean processed by steam heated. Other foods (except meat and bones meal) fitted to the linear regression model. The equations show that the digestibility of energy tends to increase with age, with the exception for soybean meal, which had higher digestibility with young birds. It follows that the age of the birds influences in the determinate of metabolizable energy value of foods. As a result of performance in the pre-starter and finishing just the feed conversion was significant. Already in starter and growth, there was significant difference in feed conversion and daily and medium weight gain. In slaughter at 42 days old, only the percentage of abdominal fat was significant